Water’s quality and environmental conditions of the hydric resources in Grajaú-MA - Ferreira, Fernando Machado; Moreira, Gleidiany da Costa; Silva, Maria Elizabete Gomes de Sousa; Silva, Ana Maria Kellen Santos; Moreira, Gardjany da Costa; Rocha, Jefferson Almeida; Passos, Ionara Nayana Gomes (Ciência e Natura, 2018)
Water is the essential element to develop and maintaining life, that is why the adoption of means of conservation of this essential resource is necessary. In Brazil, the ordinance No. 2914, from December 12th, 2011, of the Ministry Of Health establishes microbiological parameters, which determinate its quality, verifying its potability in order not to offer health risks. The research analyzed five samples from two different wells, placed in the same district of Grajaú-MA. The physical-chemical conditions were analyzed by the following parameters: total alkalinity, chlorides, total hardness, pH, iron, ammonia, chlorine, oxygen consumed, water turbidity by quick tests with the potability kit ALFAKIT and the microbiological conditions by the methodology of the multiple tubes based on the most probable number (MPN), besides seedlings on selective culture means. The results obtained in this research show that the samples of groundwater from five analyzed spots do not match the legislation, because they do not fit to the potability standards. This way, new analysis must be made, mainly microbiological and biochemical tests, to, this time on, adopt means that allow a proper treatment to this water that is used by the local communities.